THE ROLE OF THERAPEUTIC ALLIANCE IN COUNSELLING GUIDANCE FOR CHILDREN WITH SEXUAL VIOLENCE CASES IN THE SPECIAL INSTITUTION FOR CHILDREN CLASS II SUNGAI RAYA - Adela, Shisilia; Equatora, Muhammad Ali (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to identify the role of the therapeutic alliance in counseling for juvenile offenders involved in sexual violence at Lembaga Pembinaan Khusus Anak (LPKA) Class II Sungai Raya. The focus of this research is to understand how the therapeutic alliance can encourage openness among juvenile offenders, identify psychological barriers affecting their engagement in counseling, and assess its impact on the effectiveness of the rehabilitation program. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews and observations with four juvenile offenders and counselors involved in the counseling program at LPKA. The results show that a strong therapeutic alliance, built through emotional bonding, goal agreement, and collaboration in counseling tasks, plays a significant role in increasing the engagement of juvenile offenders in the counseling process. However, barriers such as feelings of shame, fear of judgment, and the limited number of counselors affect the quality of counseling. Keywords: Therapeutic Alliance; Counseling; Rehabilitation